2015
DOI: 10.1016/j.ntt.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute and developmental behavioral effects of flame retardants and related chemicals in zebrafish

Abstract: As polybrominated diphenyl ethers are phased out, numerous compounds are emerging as potential replacement flame retardants for use in consumer and electronic products. Little is known, however, about the neurobehavioral toxicity of these replacements. This study evaluated the neurobehavioral effects of acute or developmental exposure to t-butylphenyl diphenyl phosphate (BPDP), 2-ethylhexyl diphenyl phosphate (EHDP), isodecyl diphenyl phosphate (IDDP), isopropylated phenyl phosphate (IPP), tricresyl phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 84 publications
8
96
1
Order By: Relevance
“…A companion paper (Jarema et al 2015) presents information on the developmental neurotoxicity of these compounds in zebrafish. These assays are summarized in Table 2, along with additional information on the endpoints evaluated and key references for their use in toxicity screening.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A companion paper (Jarema et al 2015) presents information on the developmental neurotoxicity of these compounds in zebrafish. These assays are summarized in Table 2, along with additional information on the endpoints evaluated and key references for their use in toxicity screening.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In all cases, these decreases in spontaneous activity occurred in the absence of cytotoxicity during the 1 hour of exposure. In our companion paper, we evaluated neurobehavioral effects in zebrafish following acute and developmental exposure to these FRs (Jarema et al, 2015). Compared to the acute behavioral effects in zebrafish, in which all of the compounds were active, the MEAs detected fewer of these chemicals.…”
Section: Acute Neurotoxicitymentioning
confidence: 99%
“…At the time of our 2012 review, NTP had announced planned testing of six chemicals in this group, based on a recommendation from the U.S. Consumer Product Safety Commission (NTP 2010). Recently published studies have added to concerns about non-halogenated aromatic phosphates (Behl et al 2015; Jarema et al 2015; McGee et al 2013; Morris et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that acute exposure to relatively great concentrations of TDCIPP caused multiple toxicities (Jarema et al, 2015;Liu et al, 2016), but no information was available about multigenerational effects of environmentally relevant concentrations of TDCIPP. It has been recognized that exposure to chemicals can cause multigenerational effects through genomic and epigenetic effects.…”
Section: Discussionmentioning
confidence: 99%